2007
DOI: 10.1002/pssa.200622500
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ultraviolet photoluminescence from V‐doped ZnO thin films prepared by a sol–gel process

Abstract: Undoped and vanadium‐doped ZnO thin films were prepared on single‐crystalline p‐type Si(100) substrates by a sol–gel process and further annealed in an oxygen atmosphere. The influence of vanadium doping on the structural, surface morphological and optical properties of ZnO thin films was investigated by X‐ray diffraction, atomic force microscopy and photoluminescence measurements. Both the undoped and V‐doped ZnO thin films were of polycrystalline hexagonal wurtzite structure with (002)‐preferred orientation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The possible reason is the decrease of the density of free exciton due to the decline of the crystalline quality of ZnO thin films. In previous studies, some groups reported that appropriate doping could enhance the ultraviolet emission of ZnO thin films [29][30][31]. For example, Zhang et al [30] prepared Ag-doped ZnO thin films on Si substrates by sol-gel method and found that Ag-doping improved the ultraviolet emission.…”
Section: Resultsmentioning
confidence: 99%
“…The possible reason is the decrease of the density of free exciton due to the decline of the crystalline quality of ZnO thin films. In previous studies, some groups reported that appropriate doping could enhance the ultraviolet emission of ZnO thin films [29][30][31]. For example, Zhang et al [30] prepared Ag-doped ZnO thin films on Si substrates by sol-gel method and found that Ag-doping improved the ultraviolet emission.…”
Section: Resultsmentioning
confidence: 99%
“…The green emission centered at 510 nm is also a typical luminescence characteristic of ZnO, which has been reported in many papers. [ 28–30 ] Many researchers suggest that green emissions in the range from 490 to 525 nm are associated with the V O (oxygen vacancy) defects on ZnO surface. [ 26,31,32 ] The existence of V O defects on the ZnO in the surface layer of the ZnSnO thin film has been confirmed from the aforementioned XPS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Dopants from group II, III and transition metals are found to change the properties of ZnO films drastically. Visible emission from ZnO nanocolloids [16], ZnO films deposited by sol-gel [17], ZnO nanofibers [18], ZnO nanoparticle suspension [19], Co doped ZnO powder [20], ZnO and Pt composite nanorods [21], copper [22] and vanadium [23] doped ZnO, has been reported. Effect of oxygen pressure on green emission from pulsed laser deposited (PLD) ZnO films has been discussed by Fan et al [23], whereas quenching of green emission is reported by Zhang et al [24].…”
Section: Introductionmentioning
confidence: 99%